Smart approaches for encouraging the blood donation - Rakesh Sharma; Debadri Banerjee; Anupama Singh; Vikas Anand Saharan (Asian Journal of Transfusion Science)
Blood is a life saver in many emergencies like accidents or for the patients suffering from deadly diseases such as cancer and thalassemia. Conventionally, blood collection is done in five steps, i.e., recruitment, screening, physical examination, collection, and postdonation care. The huge demand of blood requires the implementation of smart approaches in the field of blood donation, which allows specific, measurable, achievable, and timely outcomes. This paper throws light on various smart approaches to motivate and attract people for blood donation. Gamification, social media, short message service, mobile applications, and other web-based applications are some of these approaches reviewed in this article. A number of platforms are also highlighted where one can seek potential donors or blood banks easily during urgency, avoiding the complex steps followed in traditional blood donation systems.